2022
DOI: 10.1073/pnas.2205166119
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage reduces heterogeneity and coherence of chromatin motions

Abstract: Chromatin motions depend on and may regulate genome functions, in particular the DNA damage response. In yeast, DNA double-strand breaks (DSBs) globally increase chromatin diffusion, whereas in higher eukaryotes the impact of DSBs on chromatin dynamics is more nuanced. We mapped the motions of chromatin microdomains in mammalian cells using diffractive optics and photoactivatable chromatin probes and found a high level of spatial heterogeneity. DNA damage reduces heterogeneity and imposes spatially defined shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Likewise, it was shown that the movements of H2B histones within ∼0.3 µm 2 chromatin microdomains were highly correlated. Interestingly, the correlation distances between these microdomains were up to 2 µm in the cell nucleus, spanning chromatin compartments and even beyond chromosomal territories [68]. Similarly, deep-PALM experiments emphasized the presence of spatiotemporal cross-correlations between chromatin structure and dynamics, extending several micrometers in space and tens of seconds in time [36].…”
Section: Chromatin Dynamicsmentioning
confidence: 93%
See 3 more Smart Citations
“…Likewise, it was shown that the movements of H2B histones within ∼0.3 µm 2 chromatin microdomains were highly correlated. Interestingly, the correlation distances between these microdomains were up to 2 µm in the cell nucleus, spanning chromatin compartments and even beyond chromosomal territories [68]. Similarly, deep-PALM experiments emphasized the presence of spatiotemporal cross-correlations between chromatin structure and dynamics, extending several micrometers in space and tens of seconds in time [36].…”
Section: Chromatin Dynamicsmentioning
confidence: 93%
“…Chromatin compaction was also closely correlated to constrained movement at different chromatin scales [35,43,68,104,108,109]. Heatmaps resulting from either single histone H2B tracking or tracking of H2B-bound chromatin domains showed a big heterogeneity in chromatin motion inside a nucleus, showing less movement within HC-rich regions than regions elsewhere in the genome [35,43,68,109].…”
Section: Chromatin Conformation As Proxy Of Chromatin Accessibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Changes in chromatin packing in response to DSBs and its remodelling facilitates access of the DNA repair machinery to DNA lesions [ 30 ]. Induction of DSBs leads to altered chromatin dynamics and chromatin motion that may impact the outcome of the DDR [ 31 ]. Monitoring of chromatin motion is possible using time-lapse florescence microscopy with sufficient spatial resolution [ 32 ].…”
Section: Introductionmentioning
confidence: 99%